2023
DOI: 10.3390/medicina59020227
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet Association with Serum Inflammatory Factors Stress Oxidative and Appetite in COVID-19 Patients

Abstract: Background and Objectives: The Mediterranean diet’s bioactive components are suggested to strengthen the immune system and to exert anti-inflammatory actions. This study investigated the association between adherence to the Mediterranean diet with serum inflammatory factors, total antioxidant capacity, appetite, and symptoms of COVID-19 patients. Materials and Methods: This cross-sectional study was conducted among 600 Iranian COVID-19 patients selected by a simple random method. The ten-item Mediterranean die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A flow chart of selection process and exclusion reasons is provided below (Fig 1). The study by Mohajeri et al [19] appear to meet the inclusion criteria, but were excluded, as the outcome of COVID-19, COVID-19 symptoms, or COVID-19 severity were not reported. The study only reported outcome of inflammatory biomarkers.…”
Section: Literature Searchmentioning
confidence: 99%
“…A flow chart of selection process and exclusion reasons is provided below (Fig 1). The study by Mohajeri et al [19] appear to meet the inclusion criteria, but were excluded, as the outcome of COVID-19, COVID-19 symptoms, or COVID-19 severity were not reported. The study only reported outcome of inflammatory biomarkers.…”
Section: Literature Searchmentioning
confidence: 99%
“…immune system are changes to the gut-associated lymphoid tissues arising from altered gut microflora, in response to dietary fiber, and a reduction in serum inflammatory factor levels likely due to the phenolic compounds. A very recent study, conducted among unvaccinated COVID-19 patients, aged 30 years old in Iranian hospitals, has shown that a more frequent adherence to the MD, scored by the MEDAS questionnaire, has a significant negative relationship with the symptoms of COVID-19 and serum inflammatory markers(37).…”
mentioning
confidence: 99%